All-solid-state battery

By designing the negative electrode mixture layer to contain a first phase and a second phase of specific composition in an all-solid-state battery, the problem of the halide solid electrolyte battery reacting with the negative active material and solid electrolyte during charging is solved, achieving a better cycle Features and Capacity.

CN119366018APending Publication Date: 2025-01-24TDK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380046411.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-28
Filing Date
2023-09-27
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing all-solid battery using halide-based solid electrolytes is prone to react with the negative electrode active substance and the solid electrolyte when charged, resulting in the interruption of the path of lithium ions and insufficient circulation characteristics.

Method used

An all-solid battery structure is adopted, which is composed of a negative electrode current collector, a negative electrode mixture layer and a solid electrolyte layer. The negative electrode mixture layer contains a negative electrode active material, a carbon material, a first phase and a second phase. The first phase and the second phase contain Li element and halogen element respectively, and the concentration of X element varies at different levels to prevent the decomposition of the solid electrolyte.

Benefits of technology

This structural design can effectively prevent the decomposition of the solid electrolyte, improve the cycle characteristics of the battery, and increase the discharge capacity and reversible capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119366018A_ABST
    Figure CN119366018A_ABST
Patent Text Reader

Abstract

The all-solid-state battery (100) is provided with a positive electrode layer (20), a solid electrolyte layer (10), and a negative electrode layer (30), and a negative electrode mixture layer (34) of the negative electrode layer (30) contains either or both of a negative electrode active material (34A) and a carbon material (34D), a first phase (34B) in contact with at least a portion of the negative electrode active material (34A) and the carbon material (34D), and a second phase (34C) in contact with at least a portion of the first phase (34B). The first phase (34B) and the second phase (34C) contain Li element and X element, the X element is at least one halogen element selected from F, Cl, Br and I. The X element concentration of the first phase (34B) is higher than the X element concentration of the solid electrolyte layer (10), and the X element concentration of the second phase (34C) is lower than the X element concentration of the first phase (34B) and the X element concentration of the solid electrolyte layer (10).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an all-solid-state battery.

[0002] This application claims priority based on Japanese Patent Application No. 2022-154971 filed in Japan on September 28, 2022, and the contents are incorporated herein by reference. Background Art

[0003] In recent years, with the increasing demand for portable electronic devices such as smartphones and laptops, the demand for power storage devices such as secondary batteries that serve as their power sources is also increasing. In addition, in automobiles or industrial equipment, the demand for high-capacity / high-output storage batteries is increasing. In recent years, lithium-ion secondary batteries with high energy density have attracted much attention, but flammable organic solvents are used as electrolytes in currently commercially available lithium-ion secondary batteries, which may cause fires due to short circuits. In order to solve this safety problem, a fully solid-state battery using, for example, a solid electrolyte instead of an electrolyte has been proposed. As a solid electrolyte, solid batteries using oxide solid electrolytes, sulfide solid electrolytes, and halide solid electrolytes have been proposed.

[0004] In addition, for example, Patent Document 1 and Non-Patent Document 1 disclose an all-solid battery having a sulfide solid electrolyte. Patent Document 1 discloses that in an all-solid battery having a sulfide solid electrolyte and a negative electrode active material including a carbon material, the cycle characteristics are improved by having a lithium salt coating containing fluorine on the surface of the carbon material. So far, in lithium-ion batteries using an electrolyte or all-solid batteries using a sulfide solid electrolyte such as the above, many studies have been conducted on the effects of modifying the surface of the active material.

[0005] Non-patent document 1 discloses that in an all-solid-state battery having a sulfide-based solid electrolyte and a lithium negative electrode, the interface between the sulfide-based solid electrolyte and the lithium negative electrode is stabilized by having Li2S, Li3P, or LiX between the lithium negative electrode and the solid electrolyte.

[0006] In addition, for example, Patent Document 2 and Non-Patent Document 2 disclose a lithium-ion all-solid-state battery having a halide solid electrolyte. The lithium-ion all-solid-state battery charges and discharges by inserting or deintercalating lithium ions into the positive and negative electrodes. At this time, in the lithium-ion all-solid-state battery, the electrode active material expands and contracts, and the internal resistance changes. In the all-solid-state battery of Patent Document 2, a method of coating the active material with a coating layer containing a conductive material and an inorganic solid electrolyte in order to suppress the change in internal resistance is disclosed. Specifically, the following matters are disclosed. For a mixed powder (which consists of TiSn alloy powder as negative electrode active material particles, Li 3.4 V 0.6 Si 0.4O4 powder and Ketjen black as a conductive material), and a coating treatment is performed in a planetary ball mill. After that, the coated negative electrode active material powder, Ketjen black and polyvinylidene fluoride powder are fully mixed in acetone to prepare a negative electrode paste. As a result, the surface of the negative electrode active material particles is coated with a coating layer, which is a layer containing conductive material particles in the homogeneous phase of the above-mentioned solid electrolyte. The following content is disclosed: Since the negative electrode paste is applied to the collector and dried to obtain the negative electrode, and a mechanically strong layer with a hard glassy solid electrolyte as the main component is used as a coating layer in the all-solid battery having the negative electrode, it is possible to suppress the change in battery size caused by the expansion / contraction of the active material accompanying charging and discharging, the increase in internal resistance, and the deterioration of the charging and discharging performance under large currents, thereby improving the cycle characteristics.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2011-150942

[0010] Patent Document 2: Japanese Patent Application Publication No. 2003-59492

[0011] Non-patent literature

[0012] Non-patent document 1: Electrochem, 2021, 2, pp. 452-471

[0013] Non-patent document 2: Journal of the American Chemical Society (J.Am.Chem.Soc.), 2020, 142, pp. 7012-7022 Summary of the invention

[0014] Technical problem to be solved by the invention

[0015] Oxide-based solid electrolytes, sulfide-based solid electrolytes, and halide-based solid electrolytes have different properties because of their constituent materials. In recent years, halide-based solid electrolytes have been particularly popular as solid electrolytes with high ion conductivity.

[0016] However, research on halide solid electrolytes with effective characteristics is still insufficient. All-solid batteries using halide solid electrolytes, such as those disclosed in Patent Document 2, should react with the negative electrode active material during charging, but sometimes they are prone to react with the solid electrolyte near the negative electrode. Due to the decomposition of the solid electrolyte, compounds formed by lithium ions and cations contained in the solid electrolyte will be formed near the negative electrode. The path of lithium ions flowing from the positive electrode to the negative electrode will be interrupted at the negative electrode interface. Therefore, the cycle characteristics of the all-solid battery disclosed in Patent Document 2 are not sufficient. In addition, as in the example of Li3ScCl6 in Non-Patent Document 2 (0.92Vvs.Li / Li + ) shows that there is a tendency for the potential window on the reduction side to be high, which makes it difficult to utilize on the negative electrode side. Insufficient research has been conducted on the interface between the negative electrode active material and the solid electrolyte, and between the negative electrode active material and other substances, resulting in insufficient cycle characteristics.

[0017] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide an all-solid-state battery that prevents decomposition of a solid electrolyte and exhibits excellent cycle performance.

[0018] Technical solutions for solving technical problems

[0019] In order to solve the above technical problems, the following solutions are provided.

[0020] (1) One embodiment of the present invention provides an all-solid-state battery, comprising a power generation element, the power generation element being formed by stacking a positive electrode layer, a solid electrolyte layer containing a halide solid electrolyte represented by formula (1), and a negative electrode layer in this order, the negative electrode layer comprising a negative electrode current collector and a negative electrode mixture layer provided on a surface of the negative electrode current collector opposite to the positive electrode layer, the negative electrode mixture layer comprising one or both of a negative electrode active material and a carbon material, a first phase in contact with at least a portion of the negative electrode active material and the carbon material, and a second phase in contact with at least a portion of the first phase, the first phase and the second phase comprising Li element and X element, the X element being at least one halogen element selected from the group consisting of F, Cl, Br and I, the X element concentration of the first phase being higher than the X element concentration of the solid electrolyte layer, and the X element concentration of the second phase being lower than the X element concentration of the first phase and the X element concentration of the solid electrolyte layer.

[0021] Li a E 1-b G b D c X d (1)

[0022] (In formula (1), E is at least one element selected from Al, Sc, Y, Zr, Hf, and lanthanide elements, G is at least one element selected from Na, K, Rb, Cs, Mg, Ca, Sr, Ba, B, Si, Ti, Cu, Nb, Ag, In, Sn, Sb, Ta, W, Au, and Bi, D is at least one group (anion) selected from CO3, SO4, BO3, PO4, NO3, SiO3, OH, and O2, X is at least one selected from F, Cl, Br, and I, 2≤a<3.5, 0≤b<0.5, 0≤c≤5, 0≤c≤5, 0≤c≤5, 0≤c≤5, 0≤c≤5, 0≤c≤5, 0≤c≤5, 0≤c≤5, 0≤c≤5, 0≤c≤5, 0≤b<0.5, 0≤c≤5, 0≤c≤5, 0≤c≤5, 0≤c≤5, 0≤ <d≤6.1。)

[0023] (2) In the all-solid-state battery based on the method described in (1) above, it may also be that: the first phase and the second phase further contain an E element, and the E element is at least one element selected from Al, Sc, Y, Zr, Hf and lanthanide elements, and the E element concentration of the second phase is higher than the E element concentration of the first phase.

[0024] (3) In the all-solid-state battery based on the method described in (1) or (2) above, it may also be that: the first phase and the second phase also contain a G element, and the G element is at least one element selected from Na, K, Rb, Cs, Mg, Ca, Sr, Ba, B, Si, Ti, Cu, Nb, Ag, In, Sn, Sb, Ta, W, Au, and Bi, and the G element concentration of the second phase is higher than the G element concentration of the first phase and the solid electrolyte layer.

[0025] (4) In an all-solid-state battery based on any one of the methods described in (1) to (3) above, the first phase and the second phase may also contain a D group, wherein the D group is at least one anion selected from CO3, SO4, BO3, PO4, NO3, SiO3, OH, and O2, and the D group concentration of the second phase is higher than that of the first phase and the solid electrolyte layer.

[0026] (5) In an all-solid-state battery based on any one of the methods described in (1) to (4) above, the first phase and the second phase may be in a layered structure, the first phase covers either or both of the negative electrode active material and the carbon material, and the second phase covers the first phase.

[0027] (6) In the all-solid-state battery according to any one of the above (1) to (5), the negative electrode active material may be selected from graphite, Si, SiO x , lithium titanate, and one or more of metallic lithium.

[0028] (7) In the all-solid-state battery according to any one of the above (1) to (6), the carbon material may be one or more selected from carbon black, graphite, carbon nanotubes, and graphene.

[0029] (8) In the all-solid-state battery according to any one of the above (1) to (7), the negative electrode mixture layer may contain the solid electrolyte, and the second phase may be provided between the first phase and the solid electrolyte.

[0030] Effects of the Invention

[0031] According to the above aspect, it is possible to provide an all-solid-state battery that prevents decomposition of a solid electrolyte and exhibits excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic cross-sectional view of the all-solid-state battery of this embodiment.

[0033] Figure 2 is a schematic cross-sectional view of the all-solid-state battery of this embodiment, which is Figure 1 Magnified view of the area surrounded by the dotted line.

[0034] Figure 3 yes Figure 1 An enlarged view of the vicinity of a negative electrode active material in a negative electrode mixture layer in an all-solid-state battery.

[0035] Figure 4 This is a magnified TEM image of a cross section of the all-solid-state battery of Example 1. DETAILED DESCRIPTION

[0036] Hereinafter, the present embodiment will be described in detail with reference to the accompanying drawings as appropriate. In the accompanying drawings used in the following description, in order to make the features of the present invention easy to understand, for convenience, the features are sometimes enlarged, and the size ratios of the various structural elements are sometimes different from the actual ones. The materials, dimensions, etc. illustrated in the following description are only examples, and the present invention is not limited thereto. The present embodiment can be appropriately changed to implement without changing the technical gist thereof.

[0037] [All-solid-state battery]

[0038] Figure 1 1 is a schematic cross-sectional view of the all-solid-state battery 100 according to the present embodiment. Figure 2 is a schematic cross-sectional view of the all-solid-state battery 100 of this embodiment, which is Figure 1Magnified view of the area surrounded by the double-dashed line in FIG. The all-solid-state battery 100 includes a power generation element 40, which is formed by stacking a positive electrode layer 20, a solid electrolyte layer 10 containing a halogenide solid electrolyte represented by formula (1), and a negative electrode layer 30 in this order, wherein the negative electrode layer 30 includes a negative electrode collector 32 and a negative electrode mixture layer 34 provided on a surface of the negative electrode collector 32 opposite to the positive electrode layer 20, the negative electrode mixture layer 34 includes a negative electrode active material 34A, a first phase 34B in contact with at least a portion of the negative electrode active material 34A, and a second phase 34C in contact with at least a portion of the first phase 34B, the first phase 34B and the second phase 34C contain Li element and X element, the X element being at least one halogen element selected from F, Cl, Br and I, the X element concentration of the first phase 34B is higher than the X element concentration of the solid electrolyte layer 10, and the X element concentration of the second phase 34C is lower than the X element concentration of the first phase 34B and the X element concentration of the solid electrolyte layer 10.

[0039] Li a E 1-b G b D c X d (1)

[0040] (In formula (1),

[0041] E is at least one element selected from Al, Sc, Y, Zr, Hf, and lanthanide elements,

[0042] G is at least one element selected from the group consisting of Na, K, Rb, Cs, Mg, Ca, Sr, Ba, B, Si, Ti, Cu, Nb, Ag, In, Sn, Sb, Ta, W, Au, and Bi,

[0043] D is at least one group selected from CO3, SO4, BO3, PO4, NO3, SiO3, OH, O2,

[0044] X is at least one selected from F, Cl, Br, I, 2≤a<3.5, 0≤b<0.5, 0≤c≤5, 0 <d≤6.1。)

[0045] Figure 1 The all-solid-state battery 100 shown includes a power generation element 40 and an outer casing 50. The outer casing 50 covers the periphery of the power generation element 40. The power generation element 40 is connected to the outside via a pair of terminals 60 and 62. Figure 1 Although a stacked battery is shown in FIG. 1 , a wound battery may also be used. The all-solid-state battery 100 is used for, for example, a laminated battery, a square battery, a cylindrical battery, a coin battery, a button battery, and the like.

[0046] <Power Generation Element>

[0047] The power generation element 40 includes a solid electrolyte layer 10, a positive electrode layer 20, and a negative electrode layer 30. The power generation element 40 is charged or discharged by transfer of ions between the positive electrode layer 20 and the negative electrode layer 30 via the solid electrolyte layer 10.

[0048] [Solid electrolyte layer]

[0049] The solid electrolyte layer 10 is sandwiched between the positive electrode layer 20 and the negative electrode layer 30. The solid electrolyte layer 10 contains a halide-based solid electrolyte that allows ions to move due to an externally applied electric field, etc. For example, the solid electrolyte conducts lithium ions and inhibits the movement of electrons.

[0050] The solid electrolyte is a halide-based solid electrolyte containing lithium, and a compound represented by the following formula (1) is used.

[0051] Li a E 1-b G b D c X d (1)

[0052] In the compound represented by formula (1), E is an essential component and is one of the elements forming the skeleton of the compound represented by formula (1). E is at least one element selected from Al, Sc, Y, Zr, Hf, and lanthanide elements (La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu).

[0053] The solid electrolyte having a wide potential window and high ion conductivity is obtained by containing E. As E, in order to obtain a solid electrolyte having high ion conductivity, Al, Sc, Y, Zr, Hf, and La are preferably contained, and Zr and Y are particularly preferably contained.

[0054] In the compound shown in formula (1), G is a component contained as needed. G is at least one element selected from Na, K, Rb, Cs, Mg, Ca, Sr, Ba, B, Si, Ti, Cu, Nb, Ag, In, Sn, Sb, Ta, W, Au, and Bi. In the compound shown in formula (1), G may also be a monovalent element selected from the above-mentioned Na, K, Rb, Cs, Ag, and Au. In the compound shown in formula (1), G may also be a divalent element selected from the above-mentioned Mg, Ca, Sr, Ba, Cu, and Sn. In the compound shown in formula (1), G may also be a trivalent element selected from the above-mentioned B, Si, Ti, Nb, In, Sb, Ta, W, and Bi.

[0055] In the compound represented by formula (1), D is an optionally contained component. D is at least one group selected from CO3, SO4, BO3, PO4, NO3, SiO3, OH, and O2. By containing D, the potential window on the reduction side becomes wider. D is preferably at least one group selected from SO4 and CO3, and particularly preferably SO4.

[0056] In the compound represented by formula (1), X is an essential component and is one of the elements forming the skeleton of the compound represented by formula (1). X is at least one halogen element selected from F, Cl, Br, and I. The ionic radius per valence of X is large. Therefore, by making the compound represented by formula (1) contain X, an effect of easy movement of lithium ions and high ionic conductivity can be obtained. As X, in order to obtain a solid electrolyte with high ionic conductivity, Cl is preferably contained.

[0057] In the compound represented by formula (1), a, b, c, and d are numbers satisfying 2 ≤ a < 3.5, 0 ≤ b < 0.5, 0 ≤ c ≤ 5, and 0 < d ≤ 6.1, respectively. Preferably, 2 ≤ a < 3.0, 0 ≤ b < 0.35, 0 ≤ c ≤ 3, and 1.5 < d ≤ 6.1.

[0058] Examples of the compound represented by formula (1) include Li2ZrCl6, Li2ZrSO4Cl4, Li2ZrCO3Cl4, Li3YSO4Cl4, Li3YCO3Cl4, Li2ZrSO4Cl 43.9 F 0.1 、Li2ZrSO4Cl 43.9 Br 0.1 、Li2ZrSO4Cl 43.8 I 0.2 and so on.

[0059] (Positive electrode)

[0060] As Figure 1 shown, the positive electrode layer 20 is formed by providing a positive electrode mixture layer 24 on a plate-shaped (foil-shaped) positive electrode current collector 22. The positive electrode layer 20 is configured such that the positive electrode mixture layer 24 is adjacent to the solid electrolyte layer 10 and faces the negative electrode layer 30 described later.

[0061] (Positive electrode current collector)

[0062] The positive electrode current collector 22 may be an electronically conductive material that is oxidation-resistant and not easily corroded during charging. As the positive electrode current collector 22, for example, metals such as aluminum, stainless steel, nickel, and titanium or conductive resins can be used. The positive electrode current collector 22 can also be in various forms such as powders, foils, stamped products, and extended products.

[0063] (Positive electrode mixture layer)

[0064] The positive electrode mixture layer 24 contains a positive electrode active material and, if necessary, contains a solid electrolyte, a binder, and a conductive aid.

[0065] (Positive electrode active material)

[0066] There is no particular limitation on the positive electrode active material as long as it can reversibly absorb / release and insert / extract (intercalation / deintercalation) lithium ions. As the positive electrode active material, the positive electrode active material used in the known lithium ion secondary battery can be used. As the positive electrode active material, for example, lithium-containing metal oxides, lithium-containing metal phosphates, etc. can be cited.

[0067] Examples of lithium-containing metal oxides include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), and lithium nickel oxide (LiNiO2). x Co y Mn z O2 (x + y + z = 1) represented by a composite metal oxide, lithium vanadium compounds (LiVOPO4, Li3V2(PO4)3), olivine-type LiMPO4 (wherein M represents at least one selected from Co, Ni, Mn, Fe), lithium titanate (Li4Ti5O 12 )wait.

[0068] In addition, a positive electrode active material that does not contain lithium can also be used. Examples of such positive electrode active materials include metal oxides that do not contain lithium (MnO2, V2O5, etc.), metal sulfides that do not contain lithium (MoS2, etc.), and fluorides that do not contain lithium (FeF3, VF3, etc.).

[0069] When using these positive electrode active materials that do not contain lithium, it is sufficient to dope the negative electrode with lithium ions in advance, or to use a negative electrode containing lithium ions.

[0070] (Adhesive)

[0071] The binder binds the materials constituting the positive electrode mixture layer 24 to each other. In addition, the binder binds the positive electrode mixture layer 24 and the positive electrode current collector 22. The properties required of the binder include oxidation resistance and good adhesiveness.

[0072] As the binder used for the positive electrode mixture layer 24, polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamide imide (PAI), polybenzimidazole (PBI), polyether sulfone (PES), polyacrylic acid (PA) or its copolymer, metal ion crosslinked body of polyacrylic acid (PA) or its copolymer, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, or mixtures thereof, etc. Among them, PVDF is particularly preferably used as the binder.

[0073] There is no particular limitation on the content of the binder in the positive electrode mixture layer 24. It is preferably 1% by volume to 15% by volume, and more preferably 3% by volume to 5% by volume, based on the sum of the volumes of the positive electrode active material, the solid electrolyte, the conductive aid, and the binder. If the content of the binder is too low, there is a tendency that a positive electrode layer 20 with sufficient bonding strength cannot be formed. In addition, general binders are electrochemically inactive and do not contribute to the discharge capacity. Therefore, if the content of the binder is too high, there is a tendency that it is difficult to obtain sufficient volume energy density or mass energy density.

[0074] (Conductive additive)

[0075] There is no particular limitation on the conductive additive as long as it is a substance that makes the positive electrode mixture layer 24 have good electronic conductivity, and a known conductive additive can be used. For example, carbon materials such as carbon black, graphite (natural graphite, artificial graphite), carbon nanotubes, and graphene; metals such as aluminum, copper, nickel, stainless steel, iron, and amorphous metals; conductive oxides such as ITO; or mixtures thereof. The conductive additive can also be in various forms such as powders and fibers.

[0076] There is no particular limitation on the content of the conductive aid in the positive electrode mixture layer 24. When the positive electrode mixture layer 24 contains a conductive aid, the content of the conductive aid is preferably 0.5% to 20% by volume, more preferably 1% to 10% by volume, based on the total volume of the positive electrode active material, the solid electrolyte, the conductive aid, and the binder.

[0077] (negative electrode)

[0078] The negative electrode layer 30 includes a negative electrode current collector 32 and a negative electrode mixture layer 34, and the negative electrode mixture layer 34 is provided on the surface of the negative electrode current collector 32 opposite to the positive electrode layer 20. The negative electrode mixture layer 34 includes: one or both of a negative electrode active material 34A and a carbon material 34D, a first phase 34B in contact with at least a portion of the negative electrode active material 34A and the carbon material 34D, and a second phase 34C in contact with at least a portion of the first phase 34B.

[0079] In the present embodiment, the negative electrode mixture layer 34 includes both the negative electrode active material 34A and the carbon material 34D, and the first phase 34B is in contact with at least a portion of the negative electrode active material 34A.

[0080] (Negative electrode current collector)

[0081] The negative electrode current collector 32 only needs to have electron conductivity. The negative electrode current collector 32 is, for example, a metal such as copper, aluminum, nickel, stainless steel, iron, or a conductive resin. The negative electrode current collector 32 may also be in various forms such as powder, foil, stamped product, or extended product.

[0082] (Negative electrode mixture layer)

[0083] The negative electrode mixture layer 34 contains a negative electrode active material 34A, a carbon material 34D, a first phase 34B, a second phase 34C and a solid electrolyte 34E. The solid electrolyte 34E may be contained as needed, or may not be contained. The negative electrode mixture layer 34 also contains a binder and a conductive aid as needed. As for the binder and the conductive aid, known substances can be used. The conductive aid may also be, for example, a metal. The solid electrolyte 34E is, for example, a solid electrolyte that is the same as the solid electrolyte contained in the solid electrolyte layer 10. That is, the solid electrolyte 34E is, for example, a solid electrolyte represented by the above formula (1). The second phase 34C is, for example, disposed between the first phase 34B and the solid electrolyte 34E, and is in contact with at least a portion of the first phase 34B. Figure 3 It is a schematic diagram showing an enlarged view of the vicinity of one negative electrode active material 34A in the negative electrode mixture layer 34 . Figure 2 The structure shown in FIG. 1 is that the first phase 34B covers the entire surface of the negative electrode active material 34A and the second phase 34C covers the entire surface of the first phase 34B, but the present embodiment is not limited thereto and may also be as follows: Figure 3 As shown in the enlarged view in FIG. 1 , the first phase 34B covers a portion of the surface of the negative electrode active material 34A, and the second phase 34C covers a portion of the surface of the first phase 34B.

[0084] Negative electrode active material

[0085] The negative electrode active material 34A is not particularly limited as long as it can reversibly absorb and release lithium ions and insert and extract lithium ions. As the negative electrode active material 34A, a material used in a known lithium ion secondary battery can be used.

[0086] Examples of the negative electrode active material 34A include: carbon materials such as graphite (natural graphite, artificial graphite), mesophase carbon microspheres, mesophase carbon fibers (MCF), cokes, glassy carbon, calcined organic compounds, etc.; metals that can combine with lithium, such as Si, SiO x, Sn, aluminum, etc.; their alloys; composite materials of these metals and carbon materials; lithium titanate (Li4Ti5O 12 ), SnO2 and other oxides; metallic lithium, etc. The negative electrode active material 34A is preferably selected from graphite, Si, SiO x 、Lithium titanate (Li4Ti5O 12 ) and one or more of metallic lithium.

[0087] Carbon materials

[0088] The carbon material 34D plays a role as a conductive aid and also plays a role as a negative electrode active material. The carbon material 34D is VGCF (Vapor Growth Carbon Fiber), carbon black, graphite, carbon nanotubes, graphene, etc. The carbon material 34D is preferably one or more selected from carbon black, graphite, carbon nanotubes, and graphene.

[0089] First phase

[0090] The first phase 34B contains Li element and X element, and the X element is at least one halogen element selected from F, Cl, Br and I. The X element concentration of the first phase 34B is higher than the X element concentration of the solid electrolyte layer 10. The X element concentration of the first phase 34B is, for example, more than 1 time and less than 15 times the X element concentration of the solid electrolyte layer 10, preferably more than 1 time and less than 8 times, and more preferably more than 1.2 times and less than 6.8 times. Hereinafter, the element concentration of any element refers to mass percentage.

[0091] Second phase

[0092] The second phase 34C contains Li element and X element, and the X element is at least one halogen element selected from F, Cl, Br and I. The second phase 34C, for example, contains the same element type as the first phase 34B. The X element concentration of the second phase 34C is lower than the X element concentration of the first phase 34B and the X element concentration of the solid electrolyte layer 10. The X element concentration of the second phase 34C is, for example, 0.1 times or more and less than 1 times the X element concentration of the solid electrolyte layer 10, preferably 0.3 times or more and less than 1 times, and more preferably 0.5 times or more and less than 0.98 times. The second phase 34C is, for example, sandwiched by the solid electrolyte 34E and the first phase 34B in the negative electrode mixture layer 34, or sandwiched by the solid electrolyte in the solid electrolyte layer 10 and the first phase 34B.

[0093] The first phase 34B may be in contact with at least a portion of the surface of the negative electrode active material 34A, or may be in contact with the entire surface of the negative electrode active material 34A, or may cover the entire surface of the negative electrode active material 34A.

[0094] The first phase 34B and the second phase 34C may further include an E element, which is at least one element selected from Al, Sc, Y, Zr, Hf and lanthanide elements. The concentration of the E element in the second phase 34C may be higher than that in the first phase 34B.

[0095] The first phase 34B and the second phase 34C may also contain the G element, which is at least one element selected from Na, K, Rb, Cs, Mg, Ca, Sr, Ba, B, Si, Ti, Cu, Nb, Ag, In, Sn, Sb, Ta, W, Au, and Bi. The G element concentration of the second phase 34C may also be higher than the G element concentration of the first phase 34B and the solid electrolyte layer 10.

[0096] The first phase 34B and the second phase 34C may also include a D group, which is at least one group (anion) selected from CO3, SO4, BO3, PO4, NO3, SiO3, OH, and O2. The D group concentration of the second phase may also be higher than the D group concentration of the first phase 34B and the solid electrolyte layer 10.

[0097] The first phase 34B and the second phase 34C each have a layered structure, for example. The layered structure may be discontinuous or continuous. In addition, the first phase 34B and the second phase 34C may each be partially formed into a granular state. The thickness of the second phase 34C is, for example, more than 1 / 10 times and less than 1 / 2 times the thickness of the first phase 34B. Here, regarding the thickness of the first phase 34B and the second phase 34C, the average thickness of 10 locations of each negative electrode active material 34A in the first phase 34B and the second phase 34C connected to 10 negative electrode active materials 34A in the cross-sectional image of the negative electrode mixture layer 34 is calculated.

[0098] As described above, the first phase 34B may also be at least a portion of the negative electrode active material 34A coated. Preferably, in the cross section of the negative electrode mixture layer 34 cut along the stacking direction, the first phase 34B coats an area greater than 50% and less than 100% of the area on the surface of the negative electrode active material 34A. That is, the negative electrode active material 34A in the negative electrode mixture layer 34 is an exposed area where a portion of its surface is exposed, and even if it is a coated area partially connected to the first phase 34B, the negative electrode active material 34A may be a coated area where the entire surface is connected to the first phase 34B. As long as the first phase 34B is a material having lithium ion conductivity, even if the entire surface of the negative electrode active material 34A is coated by the first phase 34B, it will not become an ion path for lithium ions. Hereinafter, the above structure is sometimes referred to as the coating rate of the first phase 34B relative to the negative electrode active material 34A. By setting the coverage rate of the first phase 34B with respect to the surface of the negative electrode active material 34A on the positive electrode layer 20 side within the above range, the effect of suppressing the reduction of the negative electrode active material 34B can be easily obtained in the covered region.

[0099] As described above, the second phase 34C is connected to at least a portion of the first phase 34B.

[0100] The cross-sectional image of the negative electrode mixture layer 34 can be confirmed by, for example, a scanning electron microscope (SEM) or a transmission electron microscope (TEM). The coverage of the phase corresponding to the composition of the first phase 34B and the second phase 34C may change during the initial charge and discharge. The coverage of the first phase and the coverage of the second phase are values ​​before the initial charge and discharge.

[0101] <Exterior body>

[0102] The outer casing 50 accommodates the power generation element 40 therein. The outer casing 50 prevents the intrusion of moisture and the like from the outside into the inside. Figure 1 As shown, the outer package 50 includes a metal foil 52 and a resin layer 54 laminated on each surface of the metal foil 52. The outer package 50 is a metal laminate film in which a polymer film (resin layer 54) is applied to the metal foil 52 from both sides.

[0103] The metal foil 52 is, for example, an aluminum foil or a stainless steel foil. As for the resin layer 54, a polymer film such as polypropylene can be used. The material constituting the resin layer 54 may be different on the inside and outside. For example, a polymer having a high melting point such as polyethylene terephthalate (PET) and polyamide (PA) can be used as the material of the outer side, and polyethylene (PE) and polypropylene (PP) can be used as the material of the polymer film on the inner side.

[0104] <Terminal>

[0105] The terminals 60 and 62 are connected to the positive electrode layer 20 and the negative electrode layer 30, respectively. The terminal 60 connected to the positive electrode layer 20 is a positive electrode terminal, and the terminal 62 connected to the negative electrode layer 30 is a negative electrode terminal. The terminals 60 and 62 are responsible for electrical connection with the outside. The terminals 60 and 62 are formed of conductive materials such as aluminum, nickel, and copper. The connection method can be welding or screw connection. From the perspective of preventing short circuits, it is preferred to protect the terminals 60 and 62 with insulating tape.

[0106] [Method for manufacturing all-solid-state battery]

[0107] Next, a method for manufacturing the all-solid-state battery of this embodiment will be described.

[0108] All-solid batteries can be manufactured using a powder molding method, for example. In the manufacturing method of an all-solid battery using a powder molding method, for example, a resin bracket having a through hole in the center and a lower punch and an upper punch are first prepared. The diameter of the through hole of the resin bracket is set to 9.99 mm, for example. The lower punch is inserted from under the through hole of the resin bracket, and a powdered solid electrolyte is thrown in from the opening side of the resin bracket. Next, an upper punch is inserted on the thrown powdered solid electrolyte, and placed on a punching machine for punching. The punching force is set to 24 tons, for example. The powdered solid electrolyte is punched by the upper punch and the lower punch in the resin bracket to form a solid electrolyte layer 10.

[0109] The powdered solid electrolyte is obtained by mixing raw material powders at a predetermined molar ratio and reacting them to obtain a target composition. Any reaction method can be used, including mechanochemical grinding, sintering, melting, liquid phase, solid phase, etc.

[0110] Next, the upper punch is temporarily removed, and the material of the positive electrode mixture layer is inserted into the upper punch side of the solid electrolyte. After that, the upper punch is inserted again for punching. The punching force is set to the same magnitude as before. The material of the positive electrode mixture layer becomes the positive electrode mixture layer 24 by punching.

[0111] Next, the lower punch is temporarily removed, and the negative electrode mixture layer material is poured into the lower punch side of the solid electrolyte layer. When pouring the negative electrode mixture layer material, for example, the sample is turned upside down and the negative electrode mixture layer material is poured onto the solid electrolyte.

[0112] In this embodiment, for example, the material of the negative electrode mixture layer is prepared according to the following method. As for the material of the negative electrode mixture layer, for example, first, the negative electrode active material, the carbon material and the solid electrolyte are mixed using a mortar and pestle made of agate to obtain a mixed powder. Then, a powder of a compound containing a lithium element and a halogen element is added to the mixed powder, and further mixed to prepare the material of the negative electrode mixture layer. The compound containing a lithium element and a halogen element is, for example, a compound represented by LiX. Here, the X element is at least one halogen element selected from F, Cl, Br and I.

[0113] Next, the lower punch is inserted again for punching. The punching force is set to the same magnitude as before. Thus, after the processing described later, a laminated body having a positive electrode mixture layer, a solid electrolyte layer, and a negative electrode mixture layer of the power generation element 40 can be formed.

[0114] Next, for example, an insulating resin sheet having a through hole in the center capable of accommodating the above-mentioned stack is prepared, and the stack is inserted in a manner that the end face of the stack is exposed. Next, metal foils serving as positive electrode collectors and negative electrode collectors are respectively arranged and fixed on the surface of the end face of the stack, thereby producing a solid battery cell. Terminals are attached to the positive electrode collector and negative electrode collector of the obtained solid battery cell, and the cells are placed in an aluminum laminate bag in a manner that the terminals are exposed, and then sealed, thereby producing a sealed cell containing a fully solid battery cell in an outer body.

[0115] In this embodiment, the sealed monomer is heat treated. When the sealed monomer is heat treated, for example, it can be treated at a temperature of 40°C to 55°C for 0.5 hours to 2 hours. By heat treating under such conditions, the all-solid-state battery 100 of the above embodiment can be manufactured, in which the first phase is formed on at least a portion of the surface of the negative electrode mixture and the second phase is formed on at least a portion of the surface of the first phase.

[0116] In the all-solid battery 100 of the present embodiment, since the negative electrode mixture layer 34 has the first phase 34B and the second phase 34C as described above, the lithium ions flowing from the positive electrode layer 20 into the negative electrode layer 30 during charging can be used to suppress the reduction of the solid electrolyte contained in the solid electrolyte layer 10 around the negative electrode layer 30. That is, in the all-solid battery 100 of the present embodiment, the reduction of the negative electrode active material 34A during charging is not hindered by the reduction of the solid electrolyte contained in the solid electrolyte layer 10. Therefore, the all-solid battery 100 of the present embodiment can increase the discharge capacity and the reversible capacity.

[0117] It is considered that the all-solid battery 100 of the present embodiment can obtain the above-mentioned effect because of the presence of the first phase 34B and the second phase 34C. Since the negative electrode mixture layer 34 has the first phase 34B and the second phase 34C, the potential of the solid electrolyte around the negative electrode layer 30 becomes low. Therefore, the reactivity of the solid electrolyte around the negative electrode layer 30 with the lithium ions flowing in from the positive electrode layer 20 during charging is reduced.

[0118] In addition, since the ion conductivity of the halide solid electrolyte used in the present embodiment is high, the ion conductivity of the all-solid battery 100 is high. In addition, the all-solid battery 100 of the present embodiment has a predetermined component element, and the first phase connected to at least a portion of the negative electrode active material and the second phase connected to at least a portion of the first phase can prevent the reduction decomposition of the solid electrolyte, and the cycle characteristics are also excellent.

[0119] Furthermore, in the above-described embodiment, a structure in which a plurality of regions are arranged in a direction intersecting the stacking direction is shown as the second phase 34C, but an integrated layered member may also be used.

[0120] As described above, the embodiments of the present invention are described in detail with reference to the accompanying drawings, but the various structures in each embodiment and their combinations are merely examples, and the structures of the present embodiment may be added, omitted, replaced, or otherwise modified without departing from the technical spirit of the present invention.

[0121] For example, in Figure 2 In the embodiment, the first phase 34B is in contact with at least a portion of the negative electrode active material 34A, but the first phase 34B may be in contact with at least a portion of the carbon material 34D. The first phase 34B may cover the entire surface of the carbon material 34D, or may cover a portion of the surface of the carbon material 34D.

[0122] In addition, Figure 2 In the embodiment, the negative electrode mixture layer 34 includes both the negative electrode active material 34A and the carbon material 34D. However, the negative electrode mixture layer 34 may include only one of the negative electrode active material 34A and the carbon material 34D.

[0123] Example

[0124] [Example 1]

[0125] (1) Preparation of solid electrolyte particles

[0126] Prepare Li2ZrCl6 powder as a solid electrolyte, and use a particle making fixture to make solid electrolyte particles. Specifically, first, as a particle making fixture, prepare a resin bracket with a diameter of 10 mm and an upper punch and a lower punch with a diameter of 9.99 mm made of die steel (SKD material). Then, insert the lower punch into the resin bracket of the particle making fixture, and put the solid electrolyte on the lower punch. Then, insert the upper punch on the solid electrolyte. Then, place the particle making fixture on a punching machine and pressurize it with a molding pressure of 24 tons. In this way, solid electrolyte particles are made.

[0127] (2) Preparation of mixture

[0128] (2-1) Preparation of positive electrode mixture

[0129] Next, prepare a positive electrode mixture. Specifically, lithium cobalt oxide (LiCoO2), the solid electrolyte (Li2ZrCl6) obtained by the above (1), and graphite (C) are weighed in a weight ratio of LiCoO2:Li2ZrCl6:C=62:35:3, and mixed for 15 minutes using an agate pestle and mortar to obtain a positive electrode mixture.

[0130] (2-2) Preparation of negative electrode mixture

[0131] Next, prepare the negative electrode mixture. Specifically, graphite (C) and solid electrolyte (Li2ZrCl6) are weighed in a weight ratio of C:Li2ZrCl6=60:40, and mixed for 15 minutes using an agate pestle and mortar, and further LiCl is added in an amount of 0.5wt% and mixed for 5 minutes to obtain a negative electrode mixture.

[0132] (3) Preparation of monomers

[0133] Next, the above-mentioned solid electrolyte particles are inserted into the resin holder of the particle production jig, and the negative electrode mixture is placed on one surface of the solid electrolyte particles. Next, the resin holder is vibrated to flatten the surface of the negative electrode mixture. Next, a lower punch is inserted on the negative electrode mixture to smooth the surface of the negative electrode mixture. Next, the direction of the solid electrolyte particles is reversed, and a positive electrode mixture is placed on the other surface of the solid electrolyte particles, and the surface of the positive electrode mixture is flattened in the same manner as the above-mentioned negative electrode mixture. Next, an upper punch is inserted on the positive electrode mixture to smooth the surface of the positive electrode mixture.

[0134] Next, a particle production jig containing the negative electrode mixture, solid electrolyte particles, and positive electrode mixture in the resin holder was placed in a punching machine and pressurized with a molding pressure of 24 tons. Next, the upper punch was temporarily removed, thereby producing a laminated body in which the negative electrode mixture particles, solid electrolyte particles, and positive electrode mixture particles were stacked in sequence. Next, a heat treatment process was performed in which the laminated body of the negative electrode mixture particles, solid electrolyte particles, and positive electrode mixture particles was kept in a constant temperature bath at 45°C for 1 hour, thereby producing the monomer of Example 1.

[0135] The monomer prepared by the above steps was sliced ​​in an environment without exposure to air, and then an electron microscope image was obtained using a transmission electron microscope (TEM). Figure 4 This is an enlarged TEM image of the negative electrode mixture layer vicinity of the cross section of the single body of Example 1. In Example 1, elemental analysis and composition analysis were performed using STEM-EDS, the presence of Li was confirmed by STEM-EELS, and crystallinity was evaluated by TEM-ED.

[0136] Specifically, for elemental analysis and composition analysis, the sample for measurement was sampled from the cross section of the thinned monomer so that the solid electrolyte layer (solid electrolyte particles) and the negative electrode mixture layer (negative electrode mixture particles) were included in the same measurement field of STEM-EDS. Linear analysis (elemental analysis and composition analysis) of the solid electrolyte, the first phase, and the second phase in the solid electrolyte layer and the negative electrode mixture layer was performed under the same conditions in the same measurement field of STEM-EDS.

[0137] In the measurement results of STEM-EELS, the Li—K absorption spectrum has two main peaks near 62 eV and 69 eV. Therefore, when the Li—K absorption spectrum having these two main peaks can be confirmed, it is determined that the Li element is present.

[0138] In the evaluation of crystallinity by TEM-ED, when diffraction spots (spots) were confirmed, it was determined that the material had crystallinity.

[0139] The results of the measurement, Figure 4 The presence of Li element was also confirmed in any of the regions marked 1 to 7 in the figure. In addition, the results of elemental analysis and composition analysis of the regions marked 1 to 7 are summarized in Table 1 (weight %). In addition, Li was not detected in EDS. In Table 1, the total amount of elements other than Li is set to 100%, and the relative amount of each element is shown. In addition, "-" in Table 1 means that the element was not confirmed. In this way, Figure 4 As shown, four layers with distinctly different compositions were confirmed in the monomer of Example 1. In addition, it was confirmed that: Figure 4 The region marked with reference numeral 1 in the figure is the negative electrode active material, the regions marked with reference numerals 2 and 3 are the first phase, the regions marked with reference numerals 4 and 5 are the second phase, and the regions marked with reference numerals 6 and 7 are the solid electrolyte (equivalent to Figure 2 34E).

[0140] The result of the linear analysis based on STEM-EDS (line profile) is a graph with the horizontal axis representing the moving distance of the measurement point (position of the measurement point) and the vertical axis representing the detection intensity (element content). In this line profile, the area with roughly the same detection intensity (element content) is determined to be any of the above four layers, and the inflection point of the graph is set as the boundary of the layer.

[0141] [Table 1]

[0142] element Region 1 Area 2 Area 3 Region 4 Area 5 Area 6 Area 7 C 97.28 2.16 - 3.21 3.57 3.15 3.03 O 1.14 5.83 6.34 30.39 30.5 26.21 26.03 S 0.17 0.88 1.85 8.67 8.31 8.14 9.1 Cl 0.24 90.66 91.81 14.03 10.9 14.05 14.49 Zr 1.16 0.46 - 43.7 46.71 48.46 47.35 total 100 100 100 100 100 100 100

[0143] In addition, the prepared monomer was used for the first charge and the first discharge, and the cycle characteristics of the monomer were obtained. In the first charge, the battery was charged to 4.2 V at 0.05 C constant current and constant voltage at 25° C. In the first discharge, the battery was discharged to 2.5 V at 0.05 C constant current at 25° C.

[0144] In addition, 1C means a current value that can be fully charged or fully discharged within 1 hour. For example, 0.5C means a current value that can be fully charged or fully discharged within 2 hours.

[0145] The cycle characteristics were measured using a secondary battery charge and discharge battery tester (manufactured by Hokuto Denko Co., Ltd.). The cycle characteristics were evaluated at 25°C. The charge and discharge were performed under the following conditions to evaluate the cycle characteristics. The battery was charged to 4.2V at a constant current and voltage of 0.5C, and then, while maintaining 4.2V, the battery was charged at a constant voltage until the current value became 0.05C. Next, the battery was discharged to 2.5V at a constant current of 1C. Under this condition, 10 cycles of charge and discharge were repeated, the discharge capacity in each cycle was compared, and the cycle characteristics were evaluated.

[0146] [Example 2]

[0147] A monomer was prepared by the same method as in Example 1 except that the powder used as the solid electrolyte was changed to Li 2 ZrSO 4 Cl 4 powder.

[0148] ·evaluate

[0149] The all-solid-state battery prepared by the above steps was sliced ​​in an atmosphere-free environment, and then an electron microscope image was obtained using a transmission electron microscope (TEM). As for the TEM image of the negative electrode mixture layer of the all-solid-state battery of Example 2, four layers were confirmed in the stacking direction as in Example 1. The composition analysis and elemental analysis described later confirmed the layers of the negative electrode active material, the first phase, the second phase, and the solid electrolyte (equivalent to Figure 2 34E). In Example 2, elemental analysis and composition analysis based on STEM-EDS were performed using TEM in the same manner as in Example 1, the presence of Li was confirmed by STEM-EELS, and the crystallinity was evaluated by TEM-ED. In addition, the prepared all-solid-state battery was used to perform the initial charge and initial discharge under the same conditions as in Example 1, and the cycle characteristics of the monomer were obtained. The initial discharge capacity of the all-solid-state battery and the cycle characteristics after 10 cycles were obtained.

[0150] [Example 3]

[0151] In Example 3, an all-solid-state battery was prepared and evaluated by the same method as in Example 2, except that the solid electrolyte was changed to Li3YCl6.

[0152] [Examples 4 to 6]

[0153] In Example 4, in addition to using Li2ZrSO4Cl 3.9 F 0.1A fully solid-state battery was prepared and evaluated by the same method as in Example 2 except that the solid electrolyte was used, the ratio of LiCl to graphite was changed to 0.4875 (wt%), and LiF was added at a ratio of 0.0125 (wt%) to graphite while adding LiCl.

[0154] In Example 5, in addition to using Li2ZrSO4Cl 3.9 Br 0.1 A fully solid-state battery was prepared and evaluated by the same method as in Example 2, except that the solid electrolyte was used, the ratio of LiCl to graphite was changed to 0.4875 (wt%), and LiBr was added at a ratio of 0.0125 (wt%) to graphite while adding LiCl.

[0155] In Example 6, in addition to using Li2ZrSO4Cl 3.8 I 0.2 A fully solid-state battery was prepared and evaluated by the same method as in Example 2, except that the solid electrolyte was used, the ratio of LiCl to graphite was changed to 0.4875 (wt%), and LiI was added at a ratio of 0.0125 (wt%) to graphite while adding LiCl.

[0156] [Examples 7 to 13]

[0157] In Example 7, an all-solid-state battery was prepared and evaluated by the same method as in Example 2, except that the solid electrolyte was changed to Li2ZrCO3Cl4.

[0158] In Example 8, in addition to changing the solid electrolyte to Li 1.5 Zr(BO3) 0.5 Except for the addition of Cl4, an all-solid-state battery was prepared and evaluated by the same method as in Example 2.

[0159] In Example 9, in addition to changing the solid electrolyte to Li 1.5 Zr(PO4) 0.5 Except for the addition of Cl4, an all-solid-state battery was prepared and evaluated by the same method as in Example 2.

[0160] In Example 10, an all-solid-state battery was prepared and evaluated by the same method as in Example 2, except that the solid electrolyte was changed to Li2Zr(NO3)Cl5.

[0161] In Example 11, an all-solid-state battery was prepared and evaluated by the same method as in Example 2, except that the solid electrolyte was changed to Li2ZrSiO3Cl4.

[0162] In Example 12, an all-solid-state battery was prepared and evaluated by the same method as in Example 2, except that the solid electrolyte was changed to Li2ZrOHCl5.

[0163] In Example 13, an all-solid-state battery was prepared and evaluated by the same method as in Example 2, except that the solid electrolyte was changed to Li2ZrOCl4.

[0164] [Example 14]

[0165] In Example 14, an all-solid-state battery was produced and evaluated by the same method as in Example 2 except that the heat treatment temperature of the sealed cell was changed to 40°C.

[0166] [Examples 15 to 17]

[0167] In Example 15, in addition to changing the solid electrolyte to Li 2.3 Zr 0.9 Cs 0.1 Except for the addition of OCl4, an all-solid-state battery was prepared and evaluated by the same method as in Example 2.

[0168] In Example 16, in addition to changing the solid electrolyte to Li 2.2 Zr 0.9 Ba 0.1 Except for the addition of OCl4, an all-solid-state battery was prepared and evaluated by the same method as in Example 2.

[0169] In Example 17, in addition to changing the solid electrolyte to Li 2.2 Zr 0.9 Ca 0.1 Except for the addition of OCl4, an all-solid-state battery was prepared and evaluated by the same method as in Example 2.

[0170] [Comparative Example 1, Comparative Example 2]

[0171] In Comparative Example 1, an all-solid-state battery was produced and evaluated by the same method as in Example 2, except that lithium chloride was not added in “(2-2) Production of negative electrode mixture” and the heat treatment step was not performed.

[0172] In Comparative Example 2, an all-solid-state battery was produced and evaluated by the same method as in Example 2 except that the heat treatment step was not performed.

[0173] [Comparative Example 3, Comparative Example 4]

[0174] In Comparative Example 3, an all-solid-state battery was produced and evaluated by the same method as in Example 3, except that lithium chloride was not added in “(2-2) Production of negative electrode mixture” and the heat treatment step was not performed.

[0175] In Comparative Example 4, an all-solid-state battery was produced and evaluated by the same method as in Example 3 except that the heat treatment step was not performed.

[0176] [Comparative Example 5, Comparative Example 6]

[0177] In Comparative Example 5, an all-solid-state battery was prepared and evaluated by the same method as in Example 1, except that lithium chloride was not added in “(2-2) Preparation of negative electrode mixture” and the heat treatment step was not performed.

[0178] In Comparative Example 6, an all-solid-state battery was produced and evaluated by the same method as in Example 1 except that the heat treatment step was not performed.

[0179] [Comparative Examples 7 to 13]

[0180] In Comparative Example 7, an all-solid-state battery was produced and evaluated by the same method as in Example 4, except that LiCl and LiF were not added in “(2-2) Production of negative electrode mixture” and the heat treatment step was not performed.

[0181] In Comparative Example 8, an all-solid-state battery was prepared and evaluated by the same method as in Example 4, except that the ratio of LiCl to graphite was changed to 0.5 (wt%), LiF was not added, and the heat treatment step was not performed.

[0182] In Comparative Example 9, an all-solid-state battery was produced and evaluated by the same method as in Example 5, except that LiCl and LiBr were not added in “(2-2) Production of negative electrode mixture” and the heat treatment step was not performed.

[0183] In Comparative Example 10, an all-solid-state battery was prepared and evaluated by the same method as in Example 5, except that the ratio of LiCl to graphite was changed to 0.5 (wt%), LiBr was not added, and the heat treatment step was not performed.

[0184] In Comparative Example 11, an all-solid-state battery was produced and evaluated by the same method as in Example 6, except that LiCl and LiI were not added in “(2-2) Production of negative electrode mixture” and the heat treatment step was not performed.

[0185] In Comparative Example 12, an all-solid-state battery was prepared and evaluated by the same method as in Example 6, except that the ratio of LiCl to graphite was changed to 0.5 (wt%), LiI was not added, and the heat treatment step was not performed.

[0186] The production conditions of the all-solid-state batteries of Examples 1 to 17 and Comparative Examples 1 to 12 are summarized in Tables 2 and 3, respectively.

[0187] In addition, the evaluation results of the all-solid-state batteries of Examples 1 to 17 and Comparative Examples 1 to 12 are summarized in Tables 4 to 6, respectively.

[0188] In Examples 1 to 17, the presence of both the first mesophase and the second mesophase was confirmed.

[0189]

[0190]

[0191]

[0192] [Table 5]

[0193]

[0194] [Table 6]

[0195]

[0196] In the table, "-" indicates the case where the experimental result is 0. As shown in Tables 4 to 6, it was confirmed that: in Examples 2 to 14, the X element concentration of the first phase is higher than the X element concentration of the solid electrolyte layer, and the X element concentration of the second phase is lower than the X element concentration of the first phase and the X element concentration of the solid electrolyte layer. In addition, it was confirmed that: the E element concentration of the second phase of Examples 2 to 14 is higher than the E element concentration of the first phase; and the D group concentration of the second phase of Examples 2, 7 to 14 is higher than the D group concentration of the first phase and the D group concentration of the solid electrolyte layer. It was confirmed that: the G element concentration of the second phase of Examples 15 to 17 is higher than the G element concentration of the first phase and the G element concentration of the solid electrolyte layer.

[0197] Here, although data related to the D group concentration and G element concentration of the solid electrolyte layer are not recorded in Table 4, the solid electrolyte layer was linearly analyzed using STEM-EDS by the above-mentioned method to measure the X element concentration, D group concentration and G element concentration of the solid electrolyte layer.

[0198] As a result of the measurement, the above matters were confirmed.

[0199] Furthermore, it was confirmed that the first discharge capacity and the cycle characteristics after 10 cycles of Examples 1 to 17 having the first phase 34B and the second phase 34C were higher than those of Comparative Examples 1 to 12 not having both the first phase 34B and the second phase 34C.

[0200] [Industrial Applicability]

[0201] The all-solid-state battery of the present embodiment can be suitably used as a secondary battery for portable electronic devices such as smartphones and notebook computers, and as a storage battery for automobiles or industrial equipment.

[0202] [Explanation of Reference Numerals]

[0203] 10: Solid electrolyte layer

[0204] 20: Positive electrode layer

[0205] 22: Positive electrode collector

[0206] 24: Positive electrode mixture layer

[0207] 30: Negative electrode layer

[0208] 32: Negative electrode collector

[0209] 34: Negative electrode mixture layer

[0210] 34A: Negative electrode active material

[0211] 34B: Phase 1

[0212] 34C: Second phase

[0213] 34D: Carbon material

[0214] 40: Power generation element

[0215] 50: Exterior body

[0216] 52: Metal foil

[0217] 54: Resin layer

[0218] 60, 62: Terminal

[0219] 100: All-solid-state battery.

Claims

1. An all-solid-state battery, wherein: A power generation element is provided, wherein a positive electrode layer, a solid electrolyte layer containing a halide solid electrolyte represented by formula (1), and a negative electrode layer are sequentially stacked, The negative electrode layer includes a negative electrode current collector and a negative electrode mixture layer provided on a surface of the negative electrode current collector facing the positive electrode layer. The negative electrode mixture layer includes one or both of a negative electrode active material and a carbon material, a first phase in contact with at least a portion of the negative electrode active material and the carbon material, and a second phase in contact with at least a portion of the first phase. The first phase and the second phase contain Li element and X element, and the X element is at least one halogen element selected from F, Cl, Br and I, The X element concentration of the first phase is higher than the X element concentration of the solid electrolyte layer, The X element concentration of the second phase is lower than the X element concentration of the first phase and the X element concentration of the solid electrolyte layer, Li a E 1-b G b D c X d (1) In formula (1), E is at least one element selected from Al, Sc, Y, Zr, Hf, and lanthanide elements, G is at least one element selected from the group consisting of Na, K, Rb, Cs, Mg, Ca, Sr, Ba, B, Si, Ti, Cu, Nb, Ag, In, Sn, Sb, Ta, W, Au, and Bi, D is at least one group selected from CO3, SO4, BO3, PO4, NO3, SiO3, OH, O2, X is at least one selected from F, Cl, Br, and I, 2≤a<3.5, 0≤b<0.5, 0≤c≤5, and 0<d≤6.

1.

2. The all-solid-state battery according to claim 1, wherein: The first phase and the second phase further contain an E element, and the E element is at least one element selected from Al, Sc, Y, Zr, Hf and lanthanide elements. The E element concentration of the second phase is higher than the E element concentration of the first phase.

3. The all-solid-state battery according to claim 1, wherein: The first phase and the second phase further contain a G element, and the G element is at least one element selected from the group consisting of Na, K, Rb, Cs, Mg, Ca, Sr, Ba, B, Si, Ti, Cu, Nb, Ag, In, Sn, Sb, Ta, W, Au, and Bi. The G element concentration of the second phase is higher than the G element concentrations of the first phase and the solid electrolyte layer.

4. The all-solid-state battery according to claim 1, wherein: The first phase and the second phase further comprise a D group, wherein the D group is at least one anion selected from CO3, SO4, BO3, PO4, NO3, SiO3, OH, and O2, The D group concentration of the second phase is higher than the D group concentrations of the first phase and the solid electrolyte layer.

5. The all-solid-state battery according to claim 1, wherein: The first phase and the second phase are in a layered structure, The first phase covers either or both of the negative electrode active material and the carbon material. The second phase covers the first phase.

6. The all-solid-state battery according to claim 1, wherein: The negative electrode active material is selected from graphite, Si, SiO x , lithium titanate, and one or more of metallic lithium.

7. The all-solid-state battery according to claim 1, wherein: The carbon material is one or more selected from carbon black, graphite, carbon nanotubes, and graphene.

8. The all-solid-state battery according to claim 1, wherein: The negative electrode mixture layer contains the solid electrolyte. The second phase is disposed between the first phase and the solid electrolyte.

Citation Information

Patent Citations

  • Lithium secondary battery and its manufacturing method

    JP2003059492A

  • Negative electrode active material and method for manufacturing the same, and all-solid lithium secondary battery and method for manufacturing the same

    JP2011150942A

  • Device, method, and program for industrial accident insurance premium management

    JP2022154971A